1992
DOI: 10.1021/j100186a030
|View full text |Cite
|
Sign up to set email alerts
|

Photodepletion spectroscopy on charge resonance band of benzene clusters (C6H6)2+ and (C6H6)3+

Abstract: Photodepletion spectra of (C&6)2+ and (c6H6)3+ are obtained from the depletion yields of the parent ions as functions of photodissociation wavelengths of 750-970 nm. The spectrum of (c6H6)2+ shows a broad and featureless band with a maximum at -920 nm and an (estimated) width of 4 0 0 0 cm-I. The spectrum of ( c, &) 3:shows a similar absorption to the (c&6)2+ band, suggesting that the (C6H6)3+ band is due to the charge resonance transition in the dimer ion subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…3,4 In the last decade, we have performed the photodissociation studies of (benzene) 2 ϩ and (benzene) 3 ϩ . [5][6][7][8][9] Figure 1 exhibits the photodissociation spectra of ͑a͒ (benzene) 2 ϩ and ͑b͒ (benzene) 3 ϩ in the 7000-28 000 cm Ϫ1 region, which were reported previously. 7,8 The spectrum of (benzene) 2 ϩ shows a very strong band at 10 930 cm Ϫ1 .…”
Section: Introductionsupporting
confidence: 61%
“…3,4 In the last decade, we have performed the photodissociation studies of (benzene) 2 ϩ and (benzene) 3 ϩ . [5][6][7][8][9] Figure 1 exhibits the photodissociation spectra of ͑a͒ (benzene) 2 ϩ and ͑b͒ (benzene) 3 ϩ in the 7000-28 000 cm Ϫ1 region, which were reported previously. 7,8 The spectrum of (benzene) 2 ϩ shows a very strong band at 10 930 cm Ϫ1 .…”
Section: Introductionsupporting
confidence: 61%
“…The character of the dimer ion core is expected to be nearly equal to the benzene dimer cation, in which the charge resonance occurs between the two equivalent benzene sites. 54 It is suggested that the charge resonance effect plays an essential role for the characteristic CH bond in the benzene dimer cation.…”
Section: B Benzene-armentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The dimer ion form is kept as a dimer ion core in some homo-molecular cluster ions, such as (benzene) n + . 13,14 However, the charge distribution of cluster ions is not predictable so easily on the basis of IE, PA, or EA. One curious manner on the charge distribution occurs for (CO 2 ) n − cluster anions, 16,20,21 which show switching of the ion core between n = 6 and 7 and between 13 and 14.…”
Section: Introductionmentioning
confidence: 99%